Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound

Intensification of extraction of curcumin from Curcuma amada using ultrasound assisted approach: Effect of different operating parameters - Shirsath, S. R.; Sable, S. S.; Gaikwad, S. G.; Sonawane, S. H.; Saini, D. R.; Gogate, P. R. (Ultrasonic Sonochemistry, 2017)
Curcumin, a dietary phytochemical, has been extracted from rhizomes of Curcuma amada using ultrasound assisted extraction (UAE) and the results compared with the conventional extraction approach to establish the process intensification benefits. The effect of operating parameters such as type of solvent, extraction time, extraction temperature, solid to solvent ratio, particle size and ultrasonic power on the extraction yield have been investigated in details for the approach UAE. The maximum extraction yield as 72% was obtained in 1 h under optimized conditions of 35 degrees C temperature, solid to solvent ratio of 1:25, particle size of 0.09 mm, ultrasonic power of 250 W and ultrasound frequency of 22 kHz with ethanol as the solvent. The obtained yield was significantly higher as compared to the batch extraction where only about 62% yield was achieved in 8 h of treatment. Peleg's model was used to describe the kinetics of UAE and the model showed a good agreement with the experimental results. Overall, ultrasound has been established to be a green process for extraction of curcumin with benefits of reduction in time as compared to batch extraction and the operating temperature as compared to Soxhlet extraction.
Keywords: Acrylamide; Cavitation; Curcumin Extraction; Design; Enhancement; Functionalized Silica; kinetics; Microwave; Nanoparticles; Natural-products; Optimization; Phenolic-compounds; Process Intensification; Solid-liquid Extraction; Ultrasound

Microwave-assisted extraction of carvone from carum carvi - Borole, O. D.; Shirsath, S. R.; Gaikwad, S. G. (Novel water treatment and separation methods simulation of chemical processes, 2017)
Due to increasing demand for potable and irrigation water, new scientific research is being conducted to deal with wastewater from a variety of sources. Novel Water Treatment and Separation Methods: Simulation of Chemical Processes presents a selection of research related to applications of chemical processes for wastewater treatment, separation techniques, and modeling and simulation of chemical processes. Among the many topics are: degradation of herbicide removal of anionic dye efficient sun-light driven photocatalysis removal of copper and iron using green activated carbon defluoridation of drinking water removal of calcium and magnesium from wastewater using ion exchange resins degradation of vegetable oil refinery wastewater novel separation techniques, including microwave-assisted extraction and more The volume presents selected examples in wastewater treatment, highlighting some recent examples of processes such as photocatalytic degradation, emulsion liquid membrane, novel photocatalyst for degradation of various pollutants, and adsorption of heavy metals. The book goes on to explore some novel separation techniques, such as microwave-assisted extraction, anhydrous ethanol through molecular sieve dehydration, batch extraction from leaves of Syzygium cumini (known as jambul, jambolan, jamblang or jamun), and reactive extraction. These novel separation techniques have proved be advantageous over conventional methods. The volume also looks at modeling and simulation of chemical processes, including chapters on flow characteristics of novel solid-liquid multistage circulating fluidized bed, mathematical modeling and simulation of gasketed plate heat exchangers, optimization of the adsorption capacity of prepared activated carbon, and modeling of ethanol/water separation by pervaporation, along with topics on simulation using CHEMCAD software.